Loanwords in the Database of Lithuanian Neologisms in the Aspect of Area of Use - Gaidienė, Anželika (Verbum, 2024)
This article aims to analyze the distribution of loanwords across various areas of use, based on data from the Database of Lithuanian Neologisms (hereinafter, the Database). The study focuses on identifying the language of origin (or mediating language) and the earliest recorded usage of these loanwords in the source. To achieve this, all 3,905 loanwords in the Database were selected and examined based on the following criteria: area of use (53 in total), language of origin (or mediating language), and earliest recorded usage. The analysis revealed that the most frequent areas of loanword usage, according to the Database, are food (12%), medicine (health) (7%), realia of other countries (7%), society (7%), lifestyle (6%), business (5%), general usage (5%), and politics (5%). English remains the dominant donor language, accounting for 69% of the loanwords. However, examining the earliest recorded usage of loanwords in each area showed that this criterion is not particularly informative for identifying distinct trends.
Keywords: loanword; area of use; language of origin; mediating language; Database of Lithuanian Neologisms